ACCOUNTING PRACTICES IN MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) IN BULELENG: PRACTITIONERS’ PERSPECTIVES AND CHALLENGES - Pasek, Nyoman Suadnyana (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
This study aims to examine the accounting practices of Micro, Small, and Medium Enterprises (MSMEs) in Buleleng, Bali, and to identify the challenges faced by practitioners in implementing proper accounting systems. Adopting a qualitative case study approach, this research involved in-depth interviews with business owners and accounting personnel from various MSMEs in the region. The findings reveal that although most MSMEs manage their accounting through basic and informal methods, significant obstacles persist, including limited accounting knowledge, restricted access to technology, and inadequate human resources. Some enterprises have attempted to mitigate these issues by attending training sessions and adopting digital accounting tools. The study emphasizes the necessity for continuous education and governmental support in improving accounting competencies and facilitating access to relevant technologies. Furthermore, the study provides practical insights for policymakers to design initiatives that can enhance the accounting capacity and sustainability of MSMEs in Buleleng.